APPLICATION OF VISIBILITY ANALYSIS AND VISUALISATION IN HOSPITAL WAYFINDING SIGN DESIGN - Mikhael Johanes; Yandi Andri Yatmo (Dimensi: Journal of Architecture and Built Environment, 2018)
This study aims to show the application of visibility analysis in hospital outpatient areas to improve wayfinding performance. Visibility is regarded as an essential aspect in wayfinding sign design and affected by the spatial configuration of the environment where the signs are located. The complexity of hospital environment prevents the designers to predict its visibility properties and also creates difficulties in determining the requirement for the sign system such as the location, direction, and size of signs. Based on isovist, visibility graph and visual catchment area (VCA) concept introduced from the past studies, we developed analytical and visualisation tools to aid the wayfinding design processes. The results suggest that the use of visibility analysis in wayfinding sign design can provide valuable insight into the preliminary analysis before the design process, as well as enable design optimisation in the development stages.